Vaccination in Nile tilapia broodstock with whole cell vaccine and disease resistance in its fry against Aeromonas hydrophila - Sukenda Sukenda; Odang Carman; Rahman Rahman; Dendi Hidayatullah; Nurfitriani Siti Yumaidawati (Jurnal Akuakultur Indonesia)
ABSTRACT